Electrical resistivity tomography determines the spatial distribution of clay layer thickness and aquifer vulnerability, Kandal Province, Cambodia. (1st October 2017) - Uhlemann, Sebastian; Kuras, Oliver; Richards, Laura A.; Naden, Emma; Polya, David A.
Graphical abstract: Highlights: Geophysical investigation applied to assess potential surface water – groundwater interactions. Laboratory and field data combined to obtain resistivity-derived lithology. Clay thickness is highly variable and may influence aquifer vulnerability. Geophysical mapping of clay layer thickness is applicable to areas of rapid urbanization. Abstract: Despite being rich in water resources, many areas of South East Asia face difficulties in securing clean water supply. This is particularly problematic in regions with a rapidly growing population. In this study, the spatial variability of the thickness of a clay layer, controlling surface – groundwater interactions that affect aquifer vulnerability, was investigated using electrical resistivity tomography (ERT). Data were acquired along two transects, showing significant differences in the imaged resistivities. Borehole samples were analyzed regarding particle density and composition, and linked to their resistivity. The obtained relationships were used to translate the field electrical resistivities into lithologies. Those revealed considerable variations in the thickness of the clay layer, ranging from 0 m up to 25 m. Geochemical data, highlighting zones of increased ingress of surface water into the groundwater, confirmed areas of discontinuities in the clay layer, which act as preferential flow paths. The results may guide urban planning of the Phnom Penh city expansion, in order to supply the growing population with safe water. The presented approach of using geophysics to estimate groundwater availability, accessibility, and vulnerability is not only applicable to Kandal Province, Cambodia, but also to many other areas of fast urbanization in South East Asia and beyond.